Missing Men: World War II Casualties and Structural Change - Christoph Eder (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2014)
This paper investigates the long-term consequences of violent conflict and the associatedhuman casualties on economic development. Using the World War II casualties suffered in Austrian municipalities as a natural experiment, I find a significant negative causal effect of human losses on economic activity, as measured by the current total wage bill in the affected communities today. The underlying determinants of this reduction in output are traced back to a lower number and density of firms, along with a smaller work force. However, this is only true for the service sector and not the manufacturing sector. As I demonstrate, the likely channel through which the effect persisted over time is through its impact on the structural composition of the work force. Specifically, greater human losses increased the fraction of employment in manufacturing at the expense of agriculture until the 1970s and services from then onwards. A simple model shows that structural change can translate a lower labor share in agricultural production into less participation of service sector growth at a later time.
Keywords: 330